A COMPARISON OF PHONOLOGY OF ENGLISH AND JAVANESE: CONTRASTIVE STUDY ON PBI STUDENTS OF UIN NORTH SUMATRA MEDAN - Damanik, Nazwa Umri; Lili Elisa Rahma; Maulana Budi Satria Siregar; Yani Lubis (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
This study aims to analyze the differences and similarities in the phonological systems of English and Javanese through a contrastive study approach among students of the English Education Department at UIN Sumatera Utara Medan. Using a qualitative descriptive method, data were collected through interviews, classroom observations, and pronunciation recordings. The results indicate significant phonological differences, especially in the articulation of /θ/, /ð/, and long vowels in English, which do not exist in the Javanese phonological system. These differences result in phonological interference that affects students’ English pronunciation. The findings underline the need for phonological awareness in English language instruction, particularly for learners with regional language backgrounds.